Penafsiran Hukum tentang “Partisipasi Langsung dalam Permusuhan” dalam Kasus-kasus Kejahatan Perang - Arlina Permanasari (Jurnal Hukum IUS QUIA IUSTUM, 2018)
Theterm  "Direct  Participation  in  Hostilities"  is  a  term  contained  in  the  1949  Geneva  Conventions  and Additional  Protocols  of  1977,  which  gave  rise  to  various  legal  interpretations.  The  two  international agreements do not provide a definition or further explanation. The problem that arises from this obscurity of interpretation is how judges conduct an analysis of whether someone can be considered as participating in an act of hostility in an armed conflict in war crimes. This research is normative with an analytical descriptive approach  towards  primary  and  secondary  legal  materials  obtained  from  literature  studies  and  analyzed qualitatively based on international humanitarian law. This research aims to identify the interpretation used in the  final  verdicts  of  international  court  on  "direct  participation  in  hostilities."  The  results  show  that  in overcoming the lack of understanding of the term, the ICRC issues an "Interpretive Guidance" that is not legally binding. Although it creates controversy and is not a legal document, the approach adopted in the "interpretive guidance" turns out to have been used as a discussion material making verdicts, but has not been fully used by the judge as a binding legal basis in war crimes.